2019
DOI: 10.1007/s41061-019-0262-3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Forces as a Synthetic Tool for Zero- and One-Dimensional Titanium Oxide-Based Nano-photocatalysts

Abstract: A new field where the utilization of mechanochemistry can create new opportunities is materials chemistry, and, more interestingly, the synthesis of novel nanomaterials. Ball-milling procedures and ultrasonic techniques can be regarded as the most important mechanochemical synthetic tools, since they can act as attractive alternatives to the conventional methods. It is also feasible for the utilization of mechanochemical forces to act synergistically with the conventional synthesis (as a pre-treatment step, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 131 publications
0
20
0
Order By: Relevance
“…3,[14][15][16][17] Highly photoactive materials are widely studied for application in environmental remediation in order to decompose/degrade hazardous compounds, but in most of the cases the outcome is complete and non-selective mineralization. 12,[17][18][19][20][21][22][23][24] The need for developing novel reactions for effective and selective valorization of organic compounds is in high demand, and two aspects can be assumed to be the most crucial: the development of a proper photoreactor and the use of a suitable photocatalyst for every specific photocatalytic reaction. Another strategy in order to elevate the photocatalytic reactions/transformations is to achieve process intensification by the application of alternative source of power.…”
Section: Introductionmentioning
confidence: 99%
“…3,[14][15][16][17] Highly photoactive materials are widely studied for application in environmental remediation in order to decompose/degrade hazardous compounds, but in most of the cases the outcome is complete and non-selective mineralization. 12,[17][18][19][20][21][22][23][24] The need for developing novel reactions for effective and selective valorization of organic compounds is in high demand, and two aspects can be assumed to be the most crucial: the development of a proper photoreactor and the use of a suitable photocatalyst for every specific photocatalytic reaction. Another strategy in order to elevate the photocatalytic reactions/transformations is to achieve process intensification by the application of alternative source of power.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] The design and development of efficient and drawback-free TiO 2 -based catalysts is still an open and challenging issue, especially when selective photo-oxidation processes are targeted. [16,17] It has been shown that such features as porosity, morphology, surface chemistry heterogeneity, and size of particles have a decisive impact on the photoreactivity. [16] Mechanochemistry applied as a synthetic tool brings an advantage of altering and tuning these surface features on demand.…”
mentioning
confidence: 99%
“…Over the past few years, low dimensional (1D or 0D) nanomaterials have been widely used in the field of photocatalysis because of their unique optical and electronic properties [79][80][81][82][83]. 1D materials have the advantages of short diffusion path and easy strain relaxation, which are beneficial to the separation of photogenerated carriers.…”
Section: D and 0d Structuresmentioning
confidence: 99%